Juvenile sex offenders: what the public needs to know - Gibson, Camille (Praeger Publishers, 2008)
When? How? And by whom? The circumstances of juvenile sex -- Explanations : what we know and don't know -- High profile cases : how on earth did this happen? -- Are all juvenile sex offenders the same? -- Unusual populations of juvenile sex offenders : females, developmentally disabled, and very young sex offenders -- Once a sex offender, always a sex offender? / guest author: Philip A. Ikomi -- Our legal response : the sex offenders you know and the ones you don't -- Putting all the pieces together : separating fact from fiction